Microbiome Composition and Microbial Community Structure in Mosquito Vectors Aedes aegypti and Aedes albopictus in Northeastern Thailand, a Dengue-Endemic Area - Rutchanee Rodpai; Patcharaporn Boonroumkaew; Lakkhana Sadaow; Oranuch Sanpool; Penchom Janwan; Tongjit Thanchomnang; Pewpan M. Intapan; Wanchai Maleewong (Insects, 2023)
Bacterial content in mosquito larvae and adults is altered by dynamic interactions during life and varies substantially in variety and composition depending on mosquito biology and ecology. This study aimed to identify the microbiota in Aedes aegypti and Aedes albopictus and in water from their breeding sites in northeastern Thailand, a dengue-endemic area. Bacterial diversity in field-collected aquatic larvae and subsequently emerged adults of both species from several locations were examined. The microbiota was characterized based on analysis of DNA sequences from the V3-V4 region of the 16S rRNA gene and exhibited changes during development, from the mosquito larval stage to the adult stage. Aedes aegypti contained a significantly higher number of bacterial genera than did Ae. albopictus, except for the genus Wolbachia, which was present at significantly higher frequencies in male Ae. albopictus (p < 0.05). Our findings also indicate likely transstadial transmission from larva to adult and give better understanding of the microbial diversity in these mosquitoes, informing future control programs against mosquito-borne diseases.